2019
DOI: 10.1016/j.jconrel.2018.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mucoinert progesterone nanosuspension for safer and more effective prevention of preterm birth

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Competing interestsThe mucus-penetrating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 70 publications
3
41
0
Order By: Relevance
“…Targeted drug delivery into the vaginal tract to prevent pre-term birth rate exploiting mucoinert progesterone nanosuspension was developed. Characteristic plasma progesterone double peak noticed in humans was also observed in pregnant mice after vaginal administration thus confirming uterine recirculation [26]. Passive targeting through PEGylation and coating with polysorbate-80 can cause deposition of apolipoprotein E on the polymeric nanoparticles, which will promote brain uptake by endothelial cells.…”
Section: Targeted Drug Deliverysupporting
confidence: 55%
“…Targeted drug delivery into the vaginal tract to prevent pre-term birth rate exploiting mucoinert progesterone nanosuspension was developed. Characteristic plasma progesterone double peak noticed in humans was also observed in pregnant mice after vaginal administration thus confirming uterine recirculation [26]. Passive targeting through PEGylation and coating with polysorbate-80 can cause deposition of apolipoprotein E on the polymeric nanoparticles, which will promote brain uptake by endothelial cells.…”
Section: Targeted Drug Deliverysupporting
confidence: 55%
“…To facilitate this, mucus-penetrating particles were developed; they are approximately 200 nm in diameter, with a net neutral surface charge, making them mucoinert (non-adhesive to mucus) and able to penetrate the cervicovaginal mucus [285]. These mucoinert nanosuspensions have been shown to improve the vaginal administration of progesterone and prevent progesterone withdrawal (RU486)-induced preterm birth in mice, while avoiding stimulating myometrial expression of inflammatory cytokines [286]. Other studies have demonstrated successful vaginal administration of the histone deacetylase inhibitors trichostatin-A (TSA) and suberoylanilide hydroxamic acid (SAHA) via mucoinert nanosuspensions [287].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…58 However, by lowering the RU486 from the typical dose of !150 mg to the minimum dose required to induce sufficiently high rates of PTB (25 mg RU486 induced 85% PTB), PTB could be prevented with vaginal progesterone. 23 Similarly, we optimized the approach for intrauterine LPS injection to achieve significant induction of PTB with lower doses. This model will be useful for studying potential therapies, including progesterone, for prevention of inflammationinduced PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone was quantified in charcoal stripped (2Â) mouse EDTA plasma (BioIVT, Westbury, NY), as previously described. 23 Briefly, progesterone was extracted from plasma with acetonitrile/n-butyl chloride containing the internal standard, progesterone-d9 (Toronto Research Chemicals, North York, ON, Canada). Samples were centrifuged, and the top layer was transferred and dried in a 40 C water bath under a stream of nitrogen gas.…”
Section: Determining Progesterone Concentration In Plasmamentioning
confidence: 99%
See 1 more Smart Citation